(untitled) (Praxis Educativa, 2026)
Numerous studies demonstrate the need to promote the development of 21st-century skills in students from an early age, in order to positively impact their overall development. In primary education, one tactic used to influence some of these skills is the integration of the following methodological strategies: STEAM projects, robotics technology, and the experimental method. This article presents a guide that groups into four categories the key points teachers should consider when integrating these methodological strategies. To this end, an exploratory ethnographic study was conducted in a school in Madrid, Spain, exploring how teachers integrate them. The most representative contributions highlight 27 key points to consider when planning, implementing, and evaluating the joint integration of the aforementioned methodological strategies.